PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP KETERAMPILAN BERBICARA SISWA KELAS IV B UPT SPF SD INPRES BORONG KOTA MAKASSAR - nur annisa; Andi Adam; Rahmatiah (STKIP Subang, 2025)
NUR ANNISA, 2025. The Effect of Using Interactive Learning Media on Speaking Skills of Fourth Grade Students of UPT SPF SD Inpres Borong, Makassar City. Thesis. Elementary School Teacher Education Study Program (PGSD S1) Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Advisor 1 Andi Adam and Advisor II Rahmatiah. The formulation of the research problem is